2002
DOI: 10.1081/clt-120006753
|View full text |Cite
|
Sign up to set email alerts
|

Methanol Poisoning Exposures in the United States: 1993–1998

Abstract: Methanol poisonings continue to occur in the United States with toddlers at the highest risk for exposure, but adolescents and adults at the highest risk for life-threatening intoxications. Over half of product-identified cases were due to consumption of windshield wiperfluid. Efforts should be undertaken to minimize methanol exposures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
1
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 15 publications
2
25
1
1
Order By: Relevance
“…Meyer et al stated that some patients, in spite of potentially lethal methanol levels of up to 160 mmol/L, did not develop signs of toxicity (5). Different from the presented case blood methanol levels were above 100mg/dL in majority (70 %) of their cases in the study of Davies et al (4), but similar to our findings metabolic acidoses and anion gap were detected in most of the cases.…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…Meyer et al stated that some patients, in spite of potentially lethal methanol levels of up to 160 mmol/L, did not develop signs of toxicity (5). Different from the presented case blood methanol levels were above 100mg/dL in majority (70 %) of their cases in the study of Davies et al (4), but similar to our findings metabolic acidoses and anion gap were detected in most of the cases.…”
Section: Discussioncontrasting
confidence: 41%
“…Davies et al (4) also indicated that toddlers were at the highest risk cluster for methanol exposure, but on the other hand adolescents and adults were at the highest risk for life-threatening intoxications in concert with investigation of clinical documents of different study which also revealed that outcomes data in toddlers resulted in comlete treatment with no sequelae (3). Drowsiness, confusion, ataxia, ocular injury, blindness, coma, seizure, and hypotension may be observed (1)(2)(3)(4)(5)(6)(7). Methanol toxicity has a more significant manifestation in that it affects the optic system more so than any of the other toxic alcohols.…”
Section: Discussionmentioning
confidence: 99%
“…Other names are methyl alcohol and wood alcohol. An increase of symptomatic cases of methanol poisoning in infants and children has been reported in the United States between 1983 and 1988; one death for every 183 methanol exposures in both children and adults has been described [9].…”
Section: Discussionmentioning
confidence: 99%
“…In children, it is usually seen after an accidental consumption of a small volume. Fatalities involving adolescents and adults are due to ingestion of larger amounts, usually in the form of attempted suicide [9]. Methanol is used as an antifreeze, a solvent and as methylated spirit.…”
Section: Introductionmentioning
confidence: 99%
“…In Norway, where methanol poisonings occurred between 2002 and 2004, nine of the 51 hospitalised patients died (Hovda, Hundreri, Tafjord, Rudberg, & Jacobsen, 2005), and so did 25 of the 111 individuals hospitalised for methanol poisoning in Estonia in 2001 (Paasma, Hovda, Tikkeberi, & Jacobsen, 2007), and four out of the 50 methanolpoisoned patients in Iran between 2000 and 2009 (Massoumi et al, 2012). In the USA, 2254 methanol poisoning cases were recorded between 1993 and 1998, and one in every 183 cases led to death (Davis, Hudson, Benson, Easom, & Coleman, 2002). In Edirne, Turkey, in 2005, almost 3% of all forensic autopsies were methanol-related (Azmak, 2006).…”
mentioning
confidence: 99%